IMPLEMENTATION OF COMMUNITY INTELLIGENCE IN EARLY DETECTION OF SECURITY AND PUBLIC ORDER DISTURBANCES AT THE CLASS I PRISON IN BANDARLAMPUNG - M Fadel Alfayed Idham; Syahrial Yuska (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study explores the implementation of correctional intelligence as a proactive strategy for early detection of security and order disturbances (kamtib) at the Class I Correctional Institution in Bandarlampung. The research is driven by systemic challenges such as overcrowding, limited personnel capacity, and the circulation of contraband, which weaken internal supervision within correctional facilities. Using a qualitative case study approach, data were collected through observations, in-depth interviews, and document analysis. The analysis is based on policy implementation theory by George C. Edwards III and intelligence theory by Sun Tzu. The findings show that correctional intelligence is implemented through three main functions: investigation, security operations, and outreach (intelligence cultivation). These functions have been initiated but are not yet optimal due to several constraints, including limited technical training, underdeveloped reporting systems, and weak coordination between units. However, persuasive interpersonal approaches in outreach activities have proven effective in obtaining important information from inmates. The study highlights the need for strategic improvements to strengthen the effectiveness of early warning systems. Key recommendations include enhancing human resource competencies, optimizing the organizational structure of correctional intelligence, and integrating information technology to improve data analysis and reporting. In addition, stronger collaboration with external law enforcement agencies is essential to build a more adaptive and anticipatory security system within correctional institutions. Keywords: Correctional Intelligence; Early Detection; Security and Order Disturbance; Overcrowding